EJBM 2021
DOI: 10.7176/ejbm/13-10-08
|View full text |Cite
|
Sign up to set email alerts
|

Lean Implementation in Jordanian Pharmaceutical Industry: The Case of Hikma Company

Abstract: The purpose of this paper was to investigate the effect of lean practices on productivity at process industries; the case of Hikma Pharmaceutical Company. A quantitative approach based on survey questionnaire was used to evaluate the impact of lean tools on productivity. The paper showed that visual management, 5S, and work standards had a significant impact on productivity, whereas, waste reduction did not have a significant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…At the end of the development of the proposal, it was possible to increase productivity by 12% and efficiency by 7% [25] Similarly, the fusion of 5S, JIT, TPM and VSM has shown that during the first five years of application, it increased efficiency by 16% in the sewing area. Based on this result, the authors explain that this is due to the fact that before the application of these tools, barriers must be considered, such as: lack of commitment from top management, outdated Lean methodologies, among others [26] Through the development of VSM and Kanban in a plastics manufacturing company, it was demonstrated that this combination helped to increase daily production by 40% [27].…”
Section: Order and Organization In Work Areasmentioning
confidence: 99%
“…At the end of the development of the proposal, it was possible to increase productivity by 12% and efficiency by 7% [25] Similarly, the fusion of 5S, JIT, TPM and VSM has shown that during the first five years of application, it increased efficiency by 16% in the sewing area. Based on this result, the authors explain that this is due to the fact that before the application of these tools, barriers must be considered, such as: lack of commitment from top management, outdated Lean methodologies, among others [26] Through the development of VSM and Kanban in a plastics manufacturing company, it was demonstrated that this combination helped to increase daily production by 40% [27].…”
Section: Order and Organization In Work Areasmentioning
confidence: 99%